Industrial Surfacing of Hammer Grinder Components Utilized in Coke-Making Process and Outlines of Surfacing Quality Improvement - Malushin N. N.; Valuev D. V. Denis Viktorovich; Osetkovsky V. L.; Valueva A. V. Anna Vladimirovna; Serikbol A. (Materials Science in Mechanical Engineering, 2015)
Title screen